Comparative Outcomes of Catheter Ablation and Antiarrhythmic Drugs in Elderly Patients with Atrial Fibrillation - Zahoor Ahmed Shah, Hafiz Muhammad Shafique, Atif Imran, Zain ul Abideen, Asim Saif Ahmad, Muhammad Zarrar Arif Butt, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
In a prospective cohort of 400 elderly patients (≥70 years) with symptomatic atrial fibrillation(AF), 200 underwent catheter ablation